Parameter estimation of micro‐motion targets for high‐range‐resolution radar using high‐order difference sequence. Issue 1 (1st February 2018) - Zhang, Wenpeng; Fu, Yaowen; Nie, Lei; Zhao, Guanhua; Yang, Wei; Yang, Jin
Abstract : Micro‐range (m‐R) signatures which are induced by micro‐motion dynamics can be observed from range profiles, providing that the range resolution of radar is high enough. For real scenarios, micro‐motion is often mixed with macro‐motion (translation). To extract the micro‐motion signatures, it is required to remove the macro‐motion component. The widely employed range alignment technique fails for rigid‐body targets with micro‐motion, since the relative distances between different scattering centres on a rigid‐body target are varying and it is unable to obtain a stable reference range profile. Thus, the extracted m‐R signatures will be accompanied with residual macro‐motion, which may lead to the degradation. However, this issue is often ignored in the research of m‐R signatures extraction. In this work, by modelling the motions of scattering centres as the superimposition of a polynomial signal (represents macro‐motion) and a sinusoidal signal (represents micro‐motion), a micro‐motion period estimation method based on high‐order difference sequence is proposed. The property that the difference operation can decrease the order of polynomial signals while preserve sinusoidal signals with the same frequency enables the proposed method to extract m‐R signatures in the presence of macro‐motion. The effectiveness of the proposed method is validated by synthetic and measured radar data.